A new finite element method for modeling delamination propagation without additional degrees of freedom. (1st July 2016) - Yamanaka, Tadayoshi; Heidari-Rarani, Mohammad; Lessard, Larry; Feret, Victor; Hubert, Pascal
Abstract: A new crack propagation modeling method via the finite element method is developed based on the strong discontinuity approach in this study. The proposed method is capable of modeling a crack within a bilinear quadrilateral element without adding extra degrees-of-freedom in order to introduce a new crack. This is done by introducing constraint equations to extrapolate the strain fields of adjacent element to the element containing a crack. Then the constraint equations are used to eliminate the degrees-of-freedom of slave nodes located at the crack faces. The errors due to no-additional degrees-of-freedom are checked by L2-norm, stresses, and strain energy release rate. The errors are compared to those of standard finite element method and are not significantly large for practical uses. To assess the proposed crack growth modeling method, delamination as an interlaminar crack in laminated composites is simulated in a double cantilever beam and compared to that of VCCT for Abaqus®. The load-opening displacement curves are in good agreement.